Perlindungan Hukum Terhadap Konsumen Atas Penjualan Obat Yang Tidak Sesuai Label - Muhammad Ferdian (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Business competition cannot be separated from fraud from business people or bad business people. Business actors who do not have the ability to compete with strong business actors are often short-minded by giving birth to policies that are not true even at the expense of consumers. So that it was treated security of medicinal products before being distributed to the market. This writing uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The procedure of data collection is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online which are then analyzed through the content analysis method (centent analysis method) with a focus on the issue of how legal protection for consumers who buy drugs not in accordance with the label, and how the legal consequences for drug products that do not meet labeling standards. From the results of the study it is known that legal protection of consumers who buy drugs that are not in accordance with the label is in the interests of the community, therefore it is the hope of all people in every country in the world to be able to make it happen.